Pembelajaran Kitab Akhlak Lil Banin dalam Meningkatkan Kecerdasan Emosional Anak di Lembaga Kesejateraan Sosial Anak Budi Mulia - Alfan Nuril Wahyudi; Siti Nur Syamsiah; Hairul Huda (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the learning of Akhlak Lil Banin in enhancing children’s emotional intelligence at the Budi Mulia Child Social Welfare Institution (LKSA). A qualitative case study approach was employed, with data collected through observation, interviews, and documentation. The research focuses on the learning process, supporting and inhibiting factors, and its impact on children’s emotional development. The results indicate that the learning of Akhlak Lil Banin is implemented in a structured and consistent manner through regular sessions and the habituation of moral values in daily life. This learning positively affects children’s emotional intelligence, particularly in emotional awareness, self-control, empathy, and social interaction. Supporting factors include the commitment of caregivers and teachers as well as a religious environment, while inhibiting factors include limited time, diverse backgrounds of children, and varying levels of discipline.